The evolution of smart sprayer system for agricultural sector in Malaysia - Shamsudin, Nur Hazahsha; Noheng, Norman Koliah Anak; Chachuli, Siti Amaniah Mohd; Selamat, Nur Asmiza; Tawai, Hrithik; Raof, Nurliyana Abdul (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This study presents the development of a smart sprayer system featuring a microcontroller, ultrasonic sensors, and a Wi-Fi module for agriculture. This system enables 360° movement capabilities and facilitates the activation and deactivation of the sprayer pump remotely. The system offers remote control functionality through smartphone integration, effectively mitigating the need for direct physical contact with hazardous chemicals during the spraying operation. The results demonstrate the efficient operation of the smart sprayer system. The average spraying efficacy is estimated to be 95%, surpassing that of conventional spraying methods, as evidenced by prior research studies. The system is accessible for remote operation via a user-friendly interface, facilitated by the integrated internet of things (IoT) and microcontroller. As anticipated, it successfully executed 360° movements, obstacle detection, water level indication, and remote control of the sprayer pump.